Somatic mutations in Brazilian patients with paroxysmal nocturnal hemoglobinuria: a comprehensive analysis - Eiko Yamakawa, Patricia; Perez Gomes, Caio; Ribeiro Mendes, Agatha; Cesar Justino de Oliveira, Caio; Porto Freitas, Florencio; Bettoni, Fabiana; Xavier dos Santos, Ernande; Campos de Molla, Vinicius; Vescovi Gonçalves, Matheus; Branquinho, Jessica; Ribeiro Nogueira, Beatriz; Bosco Pesquero, Joao; et al. (Frontiers in Medicine, 2025)
BackgroundParoxysmal nocturnal hemoglobinuria (PNH) is a rare clonal hematopoietic stem cell disease characterized by acquired abnormalities in the phosphatidylinositol glycan class A (PIG-A) gene.MethodsThis study analyzed PIG-A gene using polymerase chain reaction (PCR) followed by Sanger sequencing of 31 Brazilian patients with PNH, including 23 with classical PNH and 8 with subclinical PNH (aplastic anemia and a PNH clone).ResultsA diverse spectrum of acquired PIG-A variants was identified, encompassing insertions, deletions, and single-base substitutions. The majority of variants identified (17 out of 29) were deemed likely pathogenic for paroxysmal nocturnal hemoglobinuria (PNH). Six variants have undetermined significance (VUS) and six variants are probably benign. Somatic variants exhibited variability in type and location among the patients, with a predominance of small deletions and simple base changes. Notably, 41% of the variants were frameshift and 35% were missense. Among the 23 patients with hemolytic PNH, 19 had at least one detectable pathogenic variant. Subclinical PNH cases were characterized solely by polymorphisms.ConclusionIn conclusion, the somatic variants in Brazilian PNH patients displayed variability in both site distribution and type. Contrary to mutational hotspots observed in previous studies, none were identified in this cohort. No specific correlation between the clinical characteristics of hemolytic PNH patients and their variants was found, likely due to the extensive variety of mutations.